Punctuation power! : punctuation and how to use it - Terban, Marvin (New York : Scholastic, 2000)
Explains the purpose and importance of punctuation and how it is used, covering apostrophes, colons, commas, exclamation points, hyphens, parentheses, slashes, and more.
Includes index.
Keywords: English language -- Punctuation -- Juvenile literature; English language -- Punctuation